STUDY OF CLINICAL, LABORATORY, AND IMMUNOLOGICAL FEATURES IN PATIENTS WITH BRONCHOPULMONARY DISEASES - Kalandarova D.O, (TADQIQOTLAR, 2026)
Abstract. Bronchopulmonary diseases remain a significant medical problem due to  their  chronic  course  and  frequent  complications.  This  study  evaluates  clinical manifestations,  laboratory  findings,  and immunological parameters  in patients  with bronchopulmonary  pathology.  The  analysis  focused  on  inflammatory  activity, hematological changes, and immune system responsiveness. The findings demonstrate that early inflammatory responses and immune imbalance are common even in the initial  stages  of  the  disease,  highlighting  the  importance  of  timely  diagnosis  and individualized treatment strategies.          Diseases  of  the  bronchopulmonary  system,  such  as  chronic  bronchitis, pneumonia,  and  bronchial  asthma,  are  widely  prevalent  and  often  associated  with immune dysfunction and recurrent infections. The chronic nature of these conditions contributes to persistent inflammatory processes and alterations in the body’s defense mechanisms. Recent studies suggest that immunological disturbances play a key role in disease progression. Therefore, a comprehensive evaluation of clinical, laboratory, and immune parameters is essential for improving diagnostic accuracy and therapeutic outcomes.          The  aim  of  this  study  was  to  assess  clinical,  laboratory,  and  immunological changes in patients with bronchopulmonary diseases and to formulate evidence-based recommendations for optimizing diagnostic and treatment approaches.          The study involved 120 patients diagnosed with bronchopulmonary pathology who received inpatient treatment between 2022 and 2024. The control group included 30 apparently healthy individuals. Clinical assessment was combined with laboratory investigations, including complete blood count and biochemical analysis, as well as immunological  evaluation  of  CD4+,  CD8+,  IgA,  IgM,  and  IgG  levels.  Statistical processing was carried out using SPSS software, applying Student’s t-test, χ² test, and correlation analysis.